PENGARUH JENIS PELARUT DAN WAKTU MASERASITERHADAP KANDUNGAN SENYAWA FLAVONOID DAN AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN ALPUKAT (Persea Americana Mill) - Kemit, Nico; Rai Widarta, I Wayan; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2017)
This research was conducted to determine effect of the kinds solvent and maceration time on flavonoid content and antioxidant activity of avocado leaf extract and to obtain maceration conditions that can produce flavonoid extract with the highest antioxidant activity. The experimental design used in this research was a randomize block design, which consisted of two factors. The first factor was the kinds of solvent, which consisted of 4 kinds namely aquades, acetone 90%, ethanol 90% and methanol 90%. The second factor was the time of maceration, which consisted of 4 level namely 18, 24, 30 and 36 hours. The treatment was repeated twice to obtain 32 units of the experiment. Data were analyzed with analysis of variance, followed by Duncan test. The results showed that the best treatment of avocado leaf extract is maceration by ethanol 90% for 30 hours which the highest resulted rendemen was 27,84%, total flavonoid was 64,12 mgQE/g dry weight sampel, antioxidant activity was 82,75%, and the IC 50 value 417 mg/L.
Keywords: avocado leaf, maceration, flavonoid, antioxidant activity